STRATEGI PENGHIMPUNAN DANA (FUNDRAISING) ZAKAT, INFAQ, DAN SHADAQAH LAZNAS YATIM MANDIRI CABANG SIDOARJO - Azmiel Habibatul Hazarillah; Achmad Sjamsudin (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
Fundraising is an activity in order to collect funds from the community, both individuals, groups, organizations, and governments which will later be used to finance a program or activity of the institution so as to achieve the goals to be achieved. The purpose of this research is to find out the strategies used in raising funds in LAZNAS Yatim Mandiri Cabang Sidoarjo. This research method uses descriptive qualitative research method. The research was conducted at LAZNAS by collecting data by interview, observation, and data literature. The result of this research is that each fundraiser has its own strategy to raise funds. Keywords: fundraising, strategy, ZIS References Kasmir. 2011. Kewirausahaan. Jakarta: Rajawali Pers. Khasanah, Umrotul. 2010. Manajemen akat Modern Instrumen Pemberdayaan Ekonomi Umat. Malang: UIN-MALIKI PRE. Kemenag RI DITJEN BIMAS Islam, Direktorat Pemberdayaan Zakat, Managemen Pengelolaan Zakat, 2015. Departemen Pendidikan Nasional. Kamus Besar Bahasa Indonesia.Jakarta: Nasional Balai Pustaka. Purwanto, April. 2009. Manajemen Fundraising bagi Organisasi Pengelola Zakat. Yogyakarta: Sukses. Fakhrruddin. 2008. Fiqh dan Manajemen Zakat Di Indonesia Cetakan 1. Malang:UIN-Malang.